2019
DOI: 10.1002/anie.201910155
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2 Electroreduction to Ethylene and Multicarbon Alcohols via Electrolyte‐Driven Nanostructuring

Abstract: Production of multicarbon products (C 2+ )from CO 2 electroreduction reaction (CO 2 RR) is highly desirable for storing renewable energy and reducing carbon emission. The electrochemical synthesis of CO 2 RR catalysts that are highly selective for C 2+ products via electrolyte-driven nanostructuring is presented. Nanostructured Cu catalysts synthesized in the presence of specific anions selectively convert CO 2 into ethylene and multicarbon alcohols in aqueous 0.1m KHCO 3 solution, with the iodine-modified cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
216
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(225 citation statements)
references
References 51 publications
9
216
0
Order By: Relevance
“…This sudden change in C 2+ selectivity implies a changed reaction mechanism and can be explained by an increase in local pH due to high proton consumption at high current densities together with the phenomenon's described above. [ 65,68,69 ] The composition of the product gas stream is 37.0 vol% H 2 , 10.8 vol% CO, and 6.2 vol% ethylene along with traces of ethane (250 ppm) as well as CO 2 (Table S10, Supporting Information). However, further increasing the current density to 300 and 400 mA cm −2 , the total detected faradaic efficiency decreased significantly to 67% at 400 mA cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…This sudden change in C 2+ selectivity implies a changed reaction mechanism and can be explained by an increase in local pH due to high proton consumption at high current densities together with the phenomenon's described above. [ 65,68,69 ] The composition of the product gas stream is 37.0 vol% H 2 , 10.8 vol% CO, and 6.2 vol% ethylene along with traces of ethane (250 ppm) as well as CO 2 (Table S10, Supporting Information). However, further increasing the current density to 300 and 400 mA cm −2 , the total detected faradaic efficiency decreased significantly to 67% at 400 mA cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of specific anions can also affect the stability of Cu(I) species and the catalyst performance. In ref ( 423 ), nanostructured Cu catalysts prepared by cycling electropolished Cu foils in the presence of Cl – , Br – , I – , and CO 3 2– anions were investigated. While EXAFS analysis of all samples under CO 2 RR conditions showed a predominantly metallic structure, the HERFD-XANES method, more sensitive to the oxidation state of the catalyst, showed that Cu(I) species are present in some of the halide-modified catalysts.…”
Section: Examplesmentioning
confidence: 99%
“…A positive correlation between the amount of Cu(I) species detected by HERFD-XANES, and the yield of C 2+ products was observed. 423 In another recent study that focused on the effect of halide ions, Cu 2 O microspheres were electroreduced in the presence of iodine, which resulted in porous Cu structures. When exposed to CO 2 RR conditions, this catalyst yielded a significantly improved selectivity for C 2+ products as compared to pristine metallic Cu.…”
Section: Examplesmentioning
confidence: 99%
“…[16][17][18][19] However, the most Cu-based catalysts generally favor the production of ethylene during CO 2 RR. [20][21][22][23] To improve the selectivity of C2 + alcohols, different methods have been applied to modify the Cu-based catalysts, including modifying morphology, [24] using two metals, [25] doping with a heteroatom, [26] and modifying with other molecules. [27] These methods mainly increase the production of the key C1 intermediate (CO) by another component to further enhance the production of alcohols, because the selectivity of C2 + products can be tuned by the coverage of CO. [28] Despite these impressive efforts, the Faradaic efficiency (FE) of C2 + alcohols remains below 43 % at commercial current density (!…”
mentioning
confidence: 99%